ANALISIS DAMPAK VARIABEL PARIWISATA TERHADAP PENGEMBANGAN SEKTOR PARIWISATA DI KABUPATEN KEPULAUAN SELAYAR - Fitri, Annisa; Rusydi, Bahrul Ulum; Hasbiullah, Hasbiullah (ICOR: Journal of Regional Economics, 2021)
This study aims to determine the effect of tourism variables on the growth of the tourism sector in the Selayar Islands Regency. For this reason, the research model used is multiple regression using the ordinary least square (OLS) technique. The data used is the 2005-2019 time series data obtained from the Selayar Islands Central Statistics Agency (BPS), Selayar Islands Tourism Office, World Travel and Tourism Council (WTTC). The results showed that the influence of the development of the number of hotels and other accommodations, the number of restaurants and food stalls, and the number of tourist objects had a significant effect on the growth of the tourism sector with simultaneous testing. The results of the partial test also show that the three variables have a significant effect on the growth of the tourism industry in the Selayar Islands Regency. Keywords: Tourism, Selayar, OLS